Circulating tumor DNA: a revolutionary approach for early detection and personalized treatment of bladder cancer - Zhou, Yan; Wang, Rongzhong; Zeng, Mingtang; Liu, Sijia (Frontiers in Pharmacology, 2025)
Bladder cancer is a malignant tumor with a high global incidence and recurrence rate. Traditional diagnostic methods, such as cystoscopy and urine cytology, have limitations in sensitivity and specificity, particularly in detecting low-grade bladder cancer. Circulating tumor DNA (ctDNA) offers a non-invasive alternative, reflecting tumor genetic characteristics through blood samples. It demonstrates high sensitivity and repeatability, making it a promising tool for early detection, recurrence monitoring, and treatment evaluation. Clinical studies have shown that ctDNA not only detects tumor burden but also captures dynamic tumor mutations, aiding in personalized treatment strategies. Despite its potential, clinical implementation of ctDNA faces challenges, including optimization of detection techniques, standardization, and the cost of testing. This paper explores the role of ctDNA in advancing bladder cancer diagnosis and treatment, with a focus on refining its clinical application and guiding future research toward improved patient outcomes.